2000
DOI: 10.1093/cercor/10.9.866
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Lateralization Revealed in the Posterior Language Areas

Abstract: It has been hypothesized that language functions are more strongly lateralized to the left hemisphere in males than in females. Previous anatomical data and patient studies have suggested that the posterior language areas should exhibit sex differences. However, neuroimaging studies to date have only provided support for differences in the anterior language areas. To look for differences in the posterior language areas, functional magnetic resonance imaging scans were obtained while male and female subjects li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
122
2
5

Year Published

2004
2004
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 275 publications
(145 citation statements)
references
References 29 publications
16
122
2
5
Order By: Relevance
“…As we have argued [2], left and bilateral fusiform may be respectively optimal for males' and females' learning of a new script because of native language tuning. That is, males show left lateralization when processing native language, whereas females show bilateral activation [11,15,20]. It should be noted that our study found similar fusiform activation pattern and similar behavioral performance for males and females at the group level in learning a new language.…”
supporting
confidence: 73%
See 2 more Smart Citations
“…As we have argued [2], left and bilateral fusiform may be respectively optimal for males' and females' learning of a new script because of native language tuning. That is, males show left lateralization when processing native language, whereas females show bilateral activation [11,15,20]. It should be noted that our study found similar fusiform activation pattern and similar behavioral performance for males and females at the group level in learning a new language.…”
supporting
confidence: 73%
“…Some researchers found that males show more left-lateralized activation and females show more bilateral activation during language processing [11,15,20]. Using Xue et al's [29] paradigm and a larger sample, Chen et al further showed that the neurofunctional predictors of visual word learning effi-ciency varied between the two sexes [2].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…structural asymmetry) of the cortex. More precisely, hemispheric differences of callosal thickness and area measurements were more pronounced and significant in males than in females, which might be related to the decreased anatomical asymmetry and functional lateralization often observed in females (Lake and Bryden, 1976;Kulynych et al, 1994;Kansaku et al, 2000;Good et al, 2001;Hiscock et al, 2001;Medland et al, 2002). The present study revealed distinctive and extensive asymmetries in the anterior body and additionally in a small and less significant region in the anterior third of the CC of males.…”
Section: Discussionsupporting
confidence: 53%
“…The tendency for women to perform better on verbal tasks and men to perform better on spatial tasks appears to be related to differences in hemispheric specialization (Hiscock et al, 1995). Studies have found evidence that the superiority of women for verbal processing results from their having bilateral activation of frontal and temporal lobe regions involved in language processing, whereas men are more left lateralized for verbal processing (McGlone, 1980;Bryden, 1988;Shaywitz et al, 1995;Kimura, 1999;Kansaku et al, 2000). Gur et al (2000) found that men also show more right-lateralized activation of inferior parietal and temporal lobe regions during a visuospatial task and tend to perform better when compared to women.…”
Section: Introductionmentioning
confidence: 99%